Short Communication: Landscape composition alters parasitoid wasps but not their host diversity in tropical agricultural landscapes - Tazkiyatul Syahidah; AKHMAD RIZALI; LILIK B. PRASETYO; PUDJIANTO; DAMAYANTI BUCHORI (Society for Indonesian Biodiversity, 2020)
Abstract. Syahidah T, Rizali A, Prasetyo LB, Pudjianto, Buchori D. 2020. Short Communication: Landscape composition alters parasitoid wasps but not their host diversity in tropical agricultural landscapes. Biodiversitas 21: 1702-1706. The diversity of parasitoid wasps and their hosts in an agricultural landscape is affected by crop management and habitat conditions around crop fields. The composition of agricultural landscapes that are dominated by non-crop or natural habitats are assumed to be able to support the presence of parasitoid wasps as biological control of pests. The aim of this study was to investigate the effect of landscape composition on the diversity of parasitoid wasps and their hosts in agricultural landscapes. The research observations were conducted on six fields of long-bean cultivation located in Bogor District, West Java Province, Indonesia. Parasitoid wasps were collected by hand-collecting of their hosts (lepidopteran larvae) within 60 m distance transect to each long-bean field. In total, 17 species of parasitoid wasps and 12 species of lepidopteran larvae were found from all agricultural landscapes. A parasitoid wasp, Microplitis manilae was found in all long-bean fields (except Bantarjaya) and only parasitized the tobacco cutworm (Spodoptera litura). The tomato looper, Chrysodeixis chalcites had the highest associated parasitoids and was also parasitized by Braconidae sp5 which was also a parasitoid of S. litura. Based on the analysis results, the patch numbers of natural habitats had a positive effect on the diversity of parasitoid wasps and had no effect on the diversity of lepidopteran larvae. In conclusion, landscape compositions with patchy natural habitats have an important role to preserve beneficial insects and maintain ecosystem services in tropical agricultural landscapes.